Effects of process parameters on mechanical and metallurgical properties in high pressure die casting of AZ91 magnesium alloy - Vanli, Ali Serdar; Akdogan, Anil (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2019)
High pressure die casting (HPDC) of magnesium (Mg) alloys has been the fastest grown up and the most globally developed section in magnesium industry. HPDC of complex shape Mg alloy products have increased considerably in recent years. But low mechanical and metallurgical performance of the casting products could be experienced due to defects in HPDC of Mg alloy parts under heavy working conditions. Process technologies should be modified and process parameters need to be optimized for the use of Mg based alloy products as high performance casting parts. The correct selection of the process parameters means the correct manufacturing of the casting parts. There is a wide range of suggested process parameters for HPDC of different Mg alloys in the literature. This paper specifies optimum process parameters for the required mechanical and metallurgical properties of the die casting parts, experimentally. Experimental tests are performed by using Taguchi experimental procedure to determine the optimum process parameters in cold chamber HPDC of Mg alloy parts. Confirmation and statistical analyzing tests have confirmed the results. The results minimize the available range of process parameters in the literature for high mechanical properties and low porosity content of casting products by conducting the designed experiments in an industrial scale mass production line considering the product quality.
Keywords: Magnesium alloys; High pressure die casting; Optimum process parameters; Mechanical and metallurgical properties; Product quality; MOLTEN MAGNESIUM; TEMPERATURE; POROSITY; Engineering; Materials Science